Detection of lethal yellowing phytoplasma in coconut plantlets obtained through in vitro germination of zygotic embryos from the seeds of infected palms. (14th March 2017) - Oropeza, C.; Cordova, I.; Puch‐Hau, C.; Castillo, R.; Chan, J.L.; Sáenz, L.
Abstract: Lethal yellowing (LY) is a disease caused by 16SrIV phytoplasmas that has devastated coconut plantations in the Americas. An alternative means of phytoplasma spread is through seeds. Therefore, we used a novel approach based on plumules from the embryos of LY‐diseased coconut palms. We cultured the plumules in vitro to determine the presence of phytoplasma DNA in the plantlets. In the first assay, 185 embryos were obtained. The results showed positive detection in 20 samples (11%) with the nested PCR and in 59 samples (32%) with the TaqMan real‐time PCR. A second assay was designed to trace plumules to their respective embryos and haustorial tissues to determine whether they had derived from an embryo with positive LY detection; a total of 124 embryos were obtained. The results showed no positive detection with the nested PCR and positive detection in 42 of the haustorial tissue samples (32%) with the TaqMan real‐time PCR. The 124 plumules isolated from the embryos were cultivated under in vitro conditions and divided into two groups. Group A was followed for shoot formation and Group B was followed to the plantlet stage. After 3 months of cultivation, 33 cultures (50%) within Group A became necrotic; the rest were analysed to evaluate LY phytoplasma DNA with the TaqMan real‐time PCR assay and 14 (42%) tested positive. After 18 months of cultivation, 20 cultures (34%) within Group B became necrotic. The rest were analysed for the detection of the LY phytoplasma DNA, and 15 and 11 (39% and 29%) of the samples tested positive with the TaqMan real‐time PCR and nested PCR assays, respectively. Blast analysis of the sequenced products revealed that the sequences showed 99% homology with LY‐phytoplasma subgroup 16SrIV‐A. The results presented here demonstrate, for the first time, the occurrence of the transmission of LY phytoplasmas from coconut embryos to plantlets.